The Role of Website Quality and Interactivity toward the Formation of E-Trust, E-Satisfaction and Dual Constructs of E-Loyalty: Study on Sporting Goods E-Commerce Website PlanetSports.Asia - Adi Wahyu Anggara; I Made Bayu Dirgantara (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2022)
This study aims to analyze the effect of website quality and interactivity on the formation of e-satisfaction, e-trust, and the dual construct of e-loyalty on the sporting goods omnichannel e-commerce website PlanetSports.Asia and discuss it from the point of view of online relationship marketing theory. The research population is PlanetSports.Asia consumers who have made online purchases. This study obtained 229 responses and 190 respondents met the sample criteria. The online questionnaire was used as data collecting method and the model was estimated with Structural Equation Modeling (SEM) statistics techniques using SPSS AMOS 23. All hypotheses developed in this study were accepted.